PENGARUH KOMUNIKASI ORGANISASI DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI ( Studi Kasus pada Karyawan PT. Pegadaian (Persero) Kanwil II Pekanbaru ) - Febrina Finisia; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to analyze organizational communication and work motivation and its influence on organizational commitment to employees of PT. Pegadaian (Persero) Kanwil II Pekanbaru. The method used in this study is descriptive and quantitative using the SPSS 23. The population in this study were all employees of PT. Pegadaian (Persero) Kanwil II Area Pekanbaru totaling 156 employees. The sample used was 61 employees conducted proportionally stratified random sampling as well as methods of collecting data through questionnaires and free interviews. The results of the analysis used the validity test, reliability test, determination test, simple linear regression test, multiple linear regression test, t test and F test. So that it can be concluded that organizational communication has a positive and significant effect on organizational commitment at PT. Pegadaian (Persero) Kanwil II Pekanbaru, work motivation has a positive and significant effect on organizational commitment at PT. Pegadaian (Persero) Pekanbaru Regional Office II, and organizational communication and work motivation have a positive and significant effect on organizational commitment at PT. Pegadaian (Persero) Kanwil II Pekanbaru. Keywords: Organizational Communication, Work Motivation and Organizational               Commitment.